Structure of Macrozoobenthos Community in the Coastal Intertidal Zone, Marapalam South Coast Regency, West Sumatra - Asmawi, Dandi; Tanjung, Afrizal; Nasution, Syafrudin (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2025)
Macrobenthos is a community of organisms that spend part or all of their life cycle on the bottom of the waters, either crawling, sessile, or digging holes. This study aims to analyze the structure of the macrobenthos community in the intertidal zone of Marapalam Beach, South Coast Regency, West Sumatra Province. Sampling was carried out at three stations. Station I (mangrove), Station II (tourist spot), and Station III (fishing boat). Macrobenthos sampling used the purposive sampling method. Macrobenthos sampling at the bottom of the waters using a shovel, the substrate was filtered using a 1 mm2 mesh size sieve to separate the organism samples from the substrate. The results showed that the macrobenthos found on Marapalam Beach consisted of 2 classes and five families, five genera, and nine species of macrobenthos. The highest abundance of macrobenthos was found in the species Clypeomorus batillariaeformis. Diversity of research locations (H' 1.19), Dominance (C 0.17), Diversity (E 0.87), Clustered distribution patterns (Id 5.51), and similarity indexes of 71-100% are categorized as high species similarity